Effectiveness of India’s National Program to Save the Girl Child: Experience of Beti Bachao Beti Padao (B3P) Program from Haryana State - PAREEK, DR. ADITYA (The journal of contemporary issues in business and government, 2021)
India's government has introduced a national program to save and educate children, Beti Bachao Beti Padhao (B3P), by strict ban on sex determinant abortion prenatal Diagnostic Technique and Surgical Termination Acts of Pregnancy, and social mobilization. This research was undertaken to determine the efficacy of the intervention to increase the sex proportion at birth (SRB) in Haryana state. Prearranged SRB data (characterized as girls per 1000 boys) have been obtained for the entire state from the civil registration system. Haryana to evaluate the impact of B3P program. The study of time series regression has used to estimation the change in SRB subsequently program B3P. The sex ratio condition in Haryana has also improved over the time from 827(in 2005) to 900 (in 2016). The B3P program has successfully changed the mentally of the people towards the girl children and they also motivated to educate them in rural area. The sex ratio is also improving at various rural area of India.